The scientific author - Francis Grossmann (Revue d'anthropologie des connaissances)
This presentation connects developments in the science studies with those in scientific discourse analysis. Science studies has undergone a veritable anthropological revolution and come to pay more attention to the concrete situations in which science is elaborated in the laboratory. The focus is now on the rhetoric mobilised to convince peers or potential funding bodies, and on genres that had been heretofore neglected such as letter writing, oral exchanges, notes, memos, reports and paper submissions. A parallel renewal of linguistic and rhetorical approaches is all the more necessary because of this empirical focus: how is the writing process – with its linguistic and iconic characteristics – informed by production conditions? How is it informed by cognitive, epistemological and social issues? However, the role of the scientific author must not be forgotten as it is central to understanding scientific positioning. To succeed in initiating much-needed interdisciplinary dialogue, we need to clarify the subjects at stake – authorship and scientific discourse –, as well as their connection to linguistic and semiotic forms.